Analysis of the Influence of Business Communications and Trust on Consume Buying Decisions in Bukalapak E-Commerce (Study the Case of Stmb Students Multismart Medan) - Ferry Hidayat; Febriani Valentina (Institute of Computer Science (IOCS), 2022)
The purpose of the study was to determine the effect of business communication and trust on consumer buying decisions on the Bukalapak e-commerce on STMB MULTISMART Medan students. The research method uses descriptive quantitative. Methods of data collection using a questionnaire that will be measured using a Likert scale. The data analysis technique used is multiple linear regression analysis, partial testing, simultaneous testing and testing the coefficient of determination. The results of this study indicate that partially or simultaneously the variables of business communication and trust have a significant influence on the purchasing decisions of STMB MULTISMART students on the e-commerce website Bukalapak.